Sero-prevalence and zoonotic implication of toxoplasmosis in sheep in South Africa - McCrindle, Cheryl Myra Ethelwyn (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2006.